2022
DOI: 10.1029/2022ea002496
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Longitudinal Variation in Mid‐Latitude Ionosphere Based on CHAMP Satellite Observations

Abstract: One of the most important parts of the solar-terrestrial space environment is the ionosphere, which couples to the neutral thermosphere and is affected by various factors, including solar X-ray and extreme ultraviolet (EUV) radiations, geomagnetic activity, and waves from the lower atmosphere (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The data are derived from the International Geomagnetic Reference Field. As depicted in Figure 7, the discrepancies between geographic (gray lines) and magnetic coordinates (blue and red lines) also introduce a consid- erable modulation of the ionospheric plasma owing to the ion drag along the geomagnetic field lines (Zhang SR et al, 2011;Hu J et al, 2022). The GIM products are superposed by the spherical harmonic functions requiring substantial measurements, whereas this is insufficient for IGS station coverage over China.…”
Section: Resultsmentioning
confidence: 99%
“…The data are derived from the International Geomagnetic Reference Field. As depicted in Figure 7, the discrepancies between geographic (gray lines) and magnetic coordinates (blue and red lines) also introduce a consid- erable modulation of the ionospheric plasma owing to the ion drag along the geomagnetic field lines (Zhang SR et al, 2011;Hu J et al, 2022). The GIM products are superposed by the spherical harmonic functions requiring substantial measurements, whereas this is insufficient for IGS station coverage over China.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al, 2018). Hu et al (2022) created an empirical model through the application of principal component analysis and found that the longitudinal variations have significant season and local time dependences and hemispheric differences, owing to the geomagnetism and neutral winds. According to the Ionosphere Heat Shrinkage Theory proposed by Evans (1965), the electron temperature decreases fast after sunset, causing a decrease in the scale height.…”
mentioning
confidence: 99%